Pengenalan Dasar Augmented Reality 3D dengan Unity untuk Meningkatkan Kreativitas Pengusaha Muda - Suryopratomo, Anggit (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
The objective of the preliminary introduction of three-dimensional augmented reality (AR) with Unity is to enhance the creativity of young entrepreneurs in the Cipareuag community. This initiative is designed to address the limited understanding of young entrepreneurs regarding the utilization of 3D AR, with the objective of enhancing their knowledge and fostering innovation. This is undertaken to mitigate the challenges posed by a highly competitive market. The initiative has been meticulously designed to impart a comprehensive understanding of AR applications and Unity proficiency to these young entrepreneurs. The instructional approach adopted in this initiative encompasses a combination of material presentation and demonstration, complemented by the availability of module materials. The module is meticulously structured into five sections: (1) An introduction to AR and Unity, (2) Comprehensive instructions on downloading Unity, (3) Thorough guidelines on Unity installation, (4) Tutorials on fundamental construction, and (5) Instructions on installing AR projects on Android devices. The evaluation of the implementation of this module is based on questionnaires distributed to participants. The findings of this study demonstrated a substantial enhancement in comprehension, awareness, and entrepreneurial skills among Cipareuag youth in utilizing 3D AR employing the Unity platform, with a score of 83% in the combined Good and Very Good.